Cyclosporin-A reduced the cytotoxicity of propranolol in HUVECs via p38 MAPK signaling. Issue 4 (28th January 2022) - Lv, Zhong; Xie, Guanhao; Cui, Haowen; Yao, Zhi; Shao, Congxiang; Yuan, Weiquan; Chen, Bailing
Abstract : Abstract: Propranolol (PROP) is a nonselective β-adrenergic receptor antagonist used to treat hypertension and cardiac arrhythmias. Oral administration of PROP has recently emerged as a new treatment modality for hemangiomas. However, the side effects of PROP at the cellular level have not been adequately described. The present study investigates and highlights the mechanisms of coupling of the drugs cyclosporin-A (CyA) and PROP on cell proliferation and the occurrence of apoptosis. It also relays the antioxidant effect of PROP on human umbilical vein endothelial cells (HUVECs). HUVECs were treated with CyA and PROP. At 24 hours after treatment, the levels of reactive oxygen species (ROS), cell proliferation, and apoptosis were determined using the ROS kit, MTT assay, and Annexin V staining. In addition, the related proteins of phospho-p38 mitogen-activated protein kinase were determined by western blotting. Subsequently, HUVECs pretreated with CyA or PROP were treated with the p38 inhibitor (SB203580). Finally, the ROS level, cell proliferation, and apoptosis were measured again in both active HUVECs and HUVECs, in which the p38 proteins were inhibited. The combination of CyA and PROP reversed the effect of CyA on cell viability, reduced the ROS level and the cell apoptosis induced by PROP. Moreover, inhibition of p38 protein catalase activity immediately stopped the effect of CyA–propranolol in HUVECs. The effect of the CyA–propranolol combination on HUVECs is associated with the p38 pathway changes, which is proven to be a potential chemotherapeutic agent that minimizes the side effects of PROP in hemangioma therapy.